Towards sustainable nanomaterials: zinc phosphate nanocrystals synthesized by Bacillus subtilis - Jabur de Assis, Amanda Stefanie; Manassés Pegoraro, Guilherme; Miraveti Carriello, Giovanni; Repecka Alves, Lucas; Ramos de Oliveira, Juliana Cristina; Santos, Gabriela; Junior de Menezes, Aparecido; Pimenta Mambrini, Giovanni; Silveira Duarte, Iolanda Cristina (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
This study focuses on the synthesis of zinc phosphate nanocrystals (Zn3(PO4)2∙4H2O) using the bacterium Bacillus subtilis: a sustainable, economical and energy-efficient approach that produces biocompatible nanocrystals with controlled properties and less environmental impact. The central question investigates how biological synthesis can be a sustainable alternative to chemical and physical synthesis. The aim of this work was to demonstrate the feasibility of biological synthesis of nanocrystals, with specific objectives of evaluating their physicochemical properties, examining the efficiency of the synthesis process, analyzing the stability of the nanocrystals and exploring their potential applications in agriculture and medicine. The theoretical framework is based on the advantages of biological synthesis, including biocompatibility and sustainability. The study on the synthesis of zinc phosphate nanocrystals using the bacterium Bacillus subtilis confirmed the formation of hopeite and alpha-zinc phosphate phases, demonstrating the feasibility of biosynthesis as a green and efficient method. The physical and chemical characterization of the nanocrystals by X-ray diffractometry and scanning electron microscopy showed orthorhombic and monoclinic structures before and after calcination, respectively, with an increase in the hydrodynamic diameter of the particles. The biocompatible nanocrystals exhibited controlled physicochemical properties, highlighting their potential for applications in agriculture and medicine. The biosynthesis stood out as a sustainable, efficient approach without the use of toxic chemicals, offering an advantageous alternative to traditional methods.